The Effect of Islamic Work Ethics, Work Strees, and Work Life Balance on Employee Performance with Work Loyalty as an Intervening Variable at Bank Sumut Syariah KCP Katamso Medan - Rafika Afifah Angkat; Ahmad Perdana Indra; Khairina Tambunan (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2023)
The purpose of this study was to investigate the relationship between Islamic work ethics, workplace stress, and work-life balance, as well as the mediating role of employee loyalty, and employee performance at Bank Sumut Syariah Kcp Katamso Medan. The methodology used here is a quantitative form of survey research. For the study, researchers used a saturated sample size of 56 participants. The methodology for testing this research model uses path analysis. Employee performance was found to be positively influenced by work-life balance, positively influenced by job satisfaction, positively influenced by work stress, positively influenced by Islamic work ethics, positively influenced by work stress, positively influenced by job satisfaction, positively influenced by work-life balance, and positively influenced by Islamic work ethics. Job satisfaction does not moderate the relationship between work-life balance and productivity, nor does it moderate the impact of stress on productivity, but moderates the impact of Islamic work ethics on productivity. Employee output; Islamic work ethics significantly increase worker happiness.